Antihypertensive medications and serious fall injuries in a nationally representative sample of older adults - Tinetti, Mary E; Han, Ling; Lee, David S H; McAvay, Gail J; Peduzzi, Peter; Gross, Cary P; Zhou, Bingqing; Lin, Haiqun (JAMA internal medicine, 2014)
IMPORTANCE The effect of serious injuries, such as hip fracture and head injury, on mortality and function is comparable to that of cardiovascular events. Concerns have been raised about the risk of fall injuries in older adults taking antihypertensive medications. The low risk of fall injuries reported in clinical trials of healthy older adults may not reflect the risk in older adults with multiple chronic conditions. OBJECTIVE To determine whether antihypertensive medication use was associated with experiencing a serious fall injury in a nationally representative sample of older adults. DESIGN, PARTICIPANTS, AND SETTING Competing risk analysis as performed with propensity score adjustment and matching in the nationally representative Medicare Current Beneficiary Survey cohort during a 3-year follow-up through 2009. Participants included 4961 community-living adults older than 70 years with hypertension. EXPOSURES Antihypertensive medication intensity based on the standardized daily dose for each antihypertensive medication class that participants used. MAIN OUTCOMES AND MEASURES Serious fall injuries, including hip and other major fractures, traumatic brain injuries, and joint dislocations, ascertained through Centers for Medicare & Medicaid Services claims. RESULTS Of the 4961 participants, 14.1% received no antihypertensive medications; 54.6% were in the moderate-intensity and 31.3% in the high-intensity antihypertensive groups. During follow-up, 446 participants (9.0%) experienced serious fall injuries, and 837 (16.9%) died. The adjusted hazard ratios for serious fall injury were 1.40 (95% CI, 1.03-1.90) in the moderate-intensity and 1.28 (95% CI, 0.91-1.80) in the high-intensity antihypertensive groups compared with nonusers. Although the difference in adjusted hazard ratios across the groups did not reach statistical significance, results were similar in the propensity score-matched subcohort. Among 503 participants with a previous fall injury, the adjusted hazard ratios were 2.17 (95% CI, 0.98-4.80) for the moderate-intensity and 2.31 (95% CI, 1.01-5.29) for the high-intensity antihypertensive groups. CONCLUSIONS AND RELEVANCE Antihypertensive medications were associated with an increased risk of serious fall injuries, particularly among those with previous fall injuries. The potential harms vs benefits of antihypertensive medications should be weighed in deciding to continue treatment with antihypertensive medications in older adults with multiple chronic conditions.